Práxis em educação ambiental: uma análise de ações pedagógicas do Projeto Planeta Azul em escolas municipais de Lavras, MG - Silva, Gabriela Francine de Oliveira (2020)
With this work we intended demonstrate the importance of Environmental Education as an instrument for the realization of Sustainable Development, since its objective is to shape thinking and active citizens, able to eliminate the processes that degrade the environment and mitigate social inequalities. In this research, we aimed to analyze and discuss pedagogical practices in environmental education developed by educators from an extension project at the Federal University de Lavras, together with teachers from the municipal schools of Lavras, MG. The project, which aims to insert environmental education activities in municipal schools, was developed in 2012 by a professor with a PhD in the Business Administration and Economics Department at the Federal University of Lavras. In this project, known as Projeto Planeta Azul, we work weekly with children from the third grade of elementary school. It was observed, during the research, that through environmental education we will reach a social, cultural and economically fair Community, and for this, it is necessary to value educational actions, adequate conditions and professional training for educators so that they can work environmental education themes and activities. The results reveal that, through the intervention of the Projeto Planeta Azul, it is possible to stimulate critical thinking, develop skills and generate a transforming character in children with respect to the perception of the environment and more responsible behaviors.